Հայկական վաղմիջնադարյան քառանիստ կոթողների ուսումնասիրության արդի խնդիրները - Հակոբյան, Զարուհի («Նաիրի» հրատ.)
Armenian four-sided stelae are unique monuments of early medieval art, which were erected before the years of Arabian supremacy, but when they have emerged, is unknown. Stelae are dated from 4 till 7 or from 5 till 7 centuries, which today can not be sufficient from vocational approach. Iconographic and stylistic study of stelae‟s reliefs have an important role in the question of date. The study shows that stelae‟ images have direct parallels with the churches‟ sculptural decoration of 7 th century. It refers both Old and New Testament characters, narrative figures and ornamental decoration. One of the wrong approaches of this problem is, that, as a rule, the stelae‟ date related with Agathangelos “History” and the stela, which is described in Gregory the Illuminator‟s vision. As a result of study we can say that the stelae have emerged no earlier than 30-ies of 7 th century. This period coincide with Armenian architecture‟s “Golden Age”.
Keywords: Ճարտարապետություն; Միջնադարյան հայ մշակույթ